“Tabee Insulindia…” The Dutch colonial past - (:unkn) unknown (My University, 2018)
The colonial past of the Netherlands is particularly rich and complex. However, the nowadays Dutch society seems so have almost forgotten its colonial past.The first colonial empire originates from the era of the Dutch Revolt (1568–1648). It has both a commercial and strategic aim, i.e. diminishing the Iberian power by striking it at every point of the globe, in Asia, Africa and America. Hence, the foundation of the Dutch Republic and its colonial empire are indistinctive.If the first possessions abroad belonged to privately owned trade companies (VOC in Asia and southern Africa, and WIC in western Africa and America), the State inherits the colonial empire after the Napoleonic Wars. The newly founded Kingdom of the Netherlands, a 1815 recreation of Charles V Netherlands (comprising roughly nowadays Benelux), fails rapidly. The secession of Belgium in 1830 causes the Netherlands to adopt a policy of neutrality in Europe. The country refocuses on its colonial empire, and notably on Indonesia, in a form of ‘splendid isolation’.During the 19th century, the colonial paradigm changes, as a result of the Industrial Revolution and the intervention of the State. The mainly modest Dutch factories in Asia dating from the 17th century are the starting points of a vast territorial conquest. The Aceh War (1873–1903) is a large-scale example of the contemporary colonial policy, as is the Cultivation System (Cultuurstelsel), using from 180 onwards local land and farmers in a form of serfage for cultivating cash crops on behalf of the Dutch trading company (NHM).The Second World War is a watershed in the Dutch colonial history. In May 1940, the German invasion brutally ends more than a century of political neutrality. In 1942, Japan seizes Indonesia, ending several centuries of European military superiority. As soon as the war ends with the Japanese capitulation, a colonial war breaks out. This war (1945–1949), elusively called ‘police actions’, leads to
Keywords: African Research